Caimito (Star Apple) Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1069, a 7-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing caimito (star apple) in the home landscape. Tables include suggested cultural practices by month, fertilizer program and nutritional values. Published by the UF Department of Horticultural Sciences, January 2006.